2016
DOI: 10.1002/jcp.25469
|View full text |Cite
|
Sign up to set email alerts
|

SCD1 Alters Long-Chain Fatty Acid (LCFA) Composition and Its Expression Is Directly Regulated by SREBP-1 and PPARγ 1 in Dairy Goat Mammary Cells

Abstract: Stearoyl-CoA desaturase 1 (SCD1) is a key enzyme for the synthesis of the monounsaturated fatty acids (MUFA) palmitoleic acid and oleic acid. In non-ruminant species, SCD1 expression is known to be tightly regulated by a variety of transcription factors. Although the role of SCD1 and the transcriptional regulatory mechanism by SREBP-1 and PPARs in other species is clear, changes in lipid metabolism related to SCD1 and via the regulation of SREBP-1 or PPARG1 in ruminant mammary tissue remain largely unknown. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 84 publications
5
73
0
Order By: Relevance
“…for de novo lipogenesis H. Xu et al, 2018;Yao et al, 2017). Our experimental data provide further evidence that SREBP-1c plays a central role in regulating milk fat synthesis in BMECs.…”
Section: Discussionsupporting
confidence: 64%
“…for de novo lipogenesis H. Xu et al, 2018;Yao et al, 2017). Our experimental data provide further evidence that SREBP-1c plays a central role in regulating milk fat synthesis in BMECs.…”
Section: Discussionsupporting
confidence: 64%
“…VLCFAs regulate a variety of cellular functions and improve the resistance of numerous diseases, for instance cardiovascular disease and metabolic syndrome [1]. The enzymes involved in the process of VLCFAs synthesis were regulated by dietary [27] and transcription factors [28]. A recent study has indicated that PUFAs synthesis is regulated more by substrate competition for existing enzymes than by an increase in their mRNA expression [29].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that both PPARD and PPARG may have overlapping functions in regulating FA desaturation. The similar change in FA profiles elicited by PPARG and PPARD also suggest these 2 isotypes may share a functional PPRE in the SCD1 promoter (Yao et al, 2017). However, the fact that GW did not induce SCD1 expression strongly suggests a different PPRE binding model in the promoter for these 2 isotypes (at least for SCD1).…”
Section: Figurementioning
confidence: 90%